058 A Rare Case of Spinal and Bulbar Muscular Atrophy (SMBA) Diagnosed by Hypertestosteronemia During Infertility Treatment. (1st May 2022) - Tai, T.; Igarashi, H.; Takesige, Y.; Nakamura, Y.; Hattori, H.; Nakajo, Y.; Aono, N.; Kasajima, M.; Yoshinaga, K.; Koizumi, M.; Hashimoto, T.; Toya, M.; et al.
ABSTRACT: Introduction: Hypertestosteroneemia can be caused by a variety of diseases and drugs, some of which can cause male infertility. We report a case of spinal and bulbar muscular atrophy (SMBA) diagnosed by hypertestosteronemia during infertility treatment. Material & Methods: The patient was a 28-year-old man. His wife had no cause of infertility, did not become pregnant after 10 cycles of timed-intercourse. His semen test pointed out insufficient semen volume and asthenozoospermia. Although varicocele surgery was performed at the neighboring general hospital, semen findings did not improve. Even though two cycles of intrauterine insemination (IUI) were performed, she did not become pregnant. The couple were introduced to our clinic in November 2019. Semen findings at the first visit were same as first time. Serum hormone levels were LH 12.0 mIU / mL, FSH 3.9 mIU / mL and total testosterone 19.47 ng / mL. The testicular volume was 13 ml on both sides. SHIM: 22 points, EHS: Grade 3; the erectile function was a slight decreased. Drug-induced hypertestosteroneemia was negative. Microscopic pituitary adenoma revealed at the general hospital, but no pituitary dysfunction. The examination was conducted at the local national hospital, and a high value of CK 621 IU / L was pointed out. SMBA was suspected and the patient visited the neurology department. Finally, he had an allele of 49 CAG repeats and SMBA was diagnosed with mild bulbar palsy, weakness of the extremities Results: Even with 3 courses of IUI, she did not become pregnant and was scheduled for in vitro fertilization (IVF). At the same time as the start of IVF, the patient had a definitive diagnosis of SMBA and was scheduled for LHRH agonist treatment. Because LHRH agonists were predicted to exacerbate semen findings, we performed sperm freezing for the purpose of fertility preservation. In the initial treatment cycle of ovum pick-up, 11 oocytes were collected, and 7 mature oocytes were obtained. Five oocytes were fertilized by ICSI using frozen sperm, and four blastocysts were vitrified. After that, the second vitrified-warmed blastocyst transplantation led to pregnancy, and the pregnancy is currently ongoing. Discussion: SMBA, also known as Kennedy's Disease, affects adult men aged 30-60 years. It is a slowly progressive neuromuscular disease that causes muscle weakness, muscle atrophy, and fasciculation due to degeneration of lower motor neurons. This is a genetic disorder of X-linked recessive inheritance. It is caused by a trinucleotide repeat expansion; >40 CAG repeats, in the androgen receptor gene located on the X chromosome. Patients are mildly desensitized to androgens, causing gynecomastia, testicular atrophy, and diminished fertility. It is also accompanied by mild hypertestosteroneemia. These findings must have been the same for this patient. Conclusion: This report is the world's first report of fertility-preserving sperm freezing in SMBA patients using ejaculated sperm, and is also the first report of ICSI-induced pregnancy in frozen sperm in SMBA patients. The effectiveness of ART was suggested for SMBA patients. Disclosure: Work supported by industry: no.